Purposes of Performance Appraisal: A Systematic Review and Agenda for Future Research - Lameque, Ivan Do Carmo (2023)
Purpose: This study expands the knowledge on theoretical and practical performance appraisal purposes (PAPs) explanations. Theoretical framework: Performance Appraisal (PA) has already demonstrated its peculiar characteristic of being the foundation on which decision-making on other Human Resource (HR) policies is based, such as salary increase, training, identification and separation of poor performance. Despite that, there is a general understanding that among the criteria for measuring performance appraisal effectiveness, PAPs have been little explored by academics and researchers. However, the importance of PAPS in employees' reactions is recognized. Design/methodology/approach: Based on a systematic literature review, we synthesized 24 peer-reviewed journal papers published in the last ten years: 2012-2022. Findings: The descriptive results suggest that there has been a decrease in interest in researching on PAPs. At some time, the thematic results suggest that PAPs have been operationalized as an independent variable. Research, Practical & Social implications: Our findings broaden the understanding on PAPs in different cultural and organizational contexts, especially in Asia and Africa. On the other hand, this article can help to improve the perception of appraisers and appraisees on the usefulness of the appraisal system. This way, helping to reduce the prevailing perception that RH practices are not efficient and effective. Originality/value: The line of investigation on PAPs is aligned with previous research whose prevailing domain of administrative and development purposes is still a reality in studies on the topic. However, the novelty in this study is the growing concern with the accuracy and reliability dimension of PAPs.